Development of an automated rotating bin - Roswadi, Muhammad Aiman (2025)
The "Automated Rotating Recycling Bin" is a smart bin can that automatically rotates to the correct compartment based on the type of waste material selected by the user. Its main objective is to simplify the waste sorting process, making recycling more efficient and user-friendly. However, it may have limitations such as the need for accurate user input, potential mechanical failures, and higher costs compared to traditional bins. The design process involves identifying different waste materials, developing a sensor or user interface to detect the material type, and creating a mechanism to rotate the bin to the correct compartment. Expected results include improved recycling rates, reduced contamination of recyclable materials, and increased convenience for users, ultimately contributing to better waste management practices.